Road traffic accident mortality analysis based on time of occurrence: Evidence from Kerala, India - Vipin N; Rahul T (Elsevier, 2021)
Introduction: Road Traffic Accidents (RTA) are a global public health concern imposing huge socio-economic costs on a society. Analysis of the incidence of RTA is essential to monitor the effectiveness of different road safety policies implemented to reduce this. The present study analyzes and forecasts time zone's-specific RTA mortality reported during 2005-2018 in Kerala State, India. Methods: An aggregate level secondary time series data of the total Number of Persons Killed (NPK) due to RTA in Kerala during 2005-2018 recorded at consecutive eight time zones were considered for the analysis. The exploratory data analysis and time series regression were mainly used for analyzing the data. Results: The analysis confirms seasonality and upward trend in the RTA deaths in Kerala (549.5 (266.5660)) during 2005-2018. The minimum number of RTA deaths (129 (109,171)) happened from 00.00 a.m. to 3.00 a.m. and the maximum number of deaths occurred from 18.00 p.m. to 21.00 p.m. (810.5 (760,876)). RTA deaths in Kerala during evening and night-time were relatively higher than other time zones. RTA deaths that occurred immediately before dawn from 06.00 a.m. to 9.00 a.m. (504.5 (469,566)) or after dusk from 15.00 p.m. to 18.00 p.m. (719 (663,766)) were also relatively high in Kerala. Since 2016, in the time zones 00.00 a.m.-03.00 a.m., 09.00 a.m.-12.00 a.m., 18.00 p.m.-21.00 p.m. and 21.00 p.m.-24.00 p.m., there is an increasing trend in the RTA deaths in which during 21.00 p.m.-24.00 p.m. the NPK records a steady increase. Time series regression analysis indicates, for every 3hrs rise in time over the year; approximately four persons were killed (P-value < 0.001) due to RTA in Kerala during 2005-2018. Moreover, on average, more than 673 (P-value < 0.001) people were killed during the 18:00 p.m. - 21:00 p.m. due to RTA in Kerala than that of 00:00 a.m. - 03:00 a.m. The forecast of expected RTA deaths in Kerala based on the fitted TSR model with SAR(1)(8) errors for the years 2019-2021 indicate most road accident deaths will likely occur during 18.00 p.m. and 21.00 p.m. and the least is between 00.00 a.m. and 03.00 a.m. The forecast for 2020 shows a decrease in Kerala's RTA deaths for every time zone than 2019 and then increases in 2021. Conclusions: The findings of the study provide the evidence that there is a significant amount of increase in the RTA deaths in Kerala through time. The study insists on implementing and monitoring the road safety policies concerning specific time zones for lowering RTA death rates.